Digital technologies for financial inclusion of smallholder farmers: Needs assessment in three states of India - CGIAR Platform for Big Data in Agriculture (2019)
Study was conducted in the states of Haryana, Odisha and Tamil Nadu; using both qualitative and quantitative research.